Current recommendations for revascularization of non-infarct-related artery in patients presenting with ST-segment elevation myocardial infarction and multivessel disease - Towashiraporn, Korakoth (Frontiers in Cardiovascular Medicine, 2022)
ST-segment elevation myocardial infarction (STEMI) is a leading cause of morbidity and mortality worldwide. Immediate reperfusion therapy of the infarct-related artery (IRA) is the mainstay of treatment, either via primary percutaneous coronary intervention (PPCI) or thrombolytic therapy when PPCI is not feasible. Several studies have reported the incidence of multivessel disease (MVD) to be about 50% of total STEMI cases. This means that after successful PPCI of the IRA, residual lesion(s) of the non-IRA may persist. Unlike the atherosclerotic plaque of stable coronary artery disease, the residual obstructive lesion of the non-IRA contains a significantly higher prevalence of vulnerable plaques. Since these lesions are a strong predictor of acute coronary syndrome, if left untreated they are a possible cause of future adverse cardiovascular events. Percutaneous coronary intervention (PCI) of the obstructive lesion of the non-IRA to achieve complete revascularization (CR) is therefore preferable. Several major randomized controlled trials (RCTs) and meta-analyses demonstrated the clinical benefits of the CR strategy in the setting of STEMI with MVD, not only for enhancing survival but also for reducing unplanned revascularization. The CR strategy is now supported by recently published clinical practice guidelines. Nevertheless, the benefit of revascularization must be weighed against the risks from additional procedures.